Pengembangan Penggunaan Aplikasi Pembelajaran Ebook Tajwid Reader dalam Mata Pelajaran Ilmu Tajwid di Pondok Pesantren Darussalam Kota Bengkulu - Ilfad Ramadhan (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
This study aims to develop the use of the Tajweed Reader Ebook Learning Application in Tajweed Science Subjects at the Darussalam Islamic Boarding School, Bengkulu City. To reveal this problem in depth and comprehensively, the researcher used a type of research and development (Research and Development) with the stages of development covering the stages of product analysis to be developed, developing initial products, expert validation and revision, small group trials and revisions and product trials. The subject of this research is a trial of the product being developed, namely the Darussalam Islamic Boarding School students, Bengkulu City. The data collection method used is Observation, Using Questionnaire Instruments, Test Methods. The data obtained were then analyzed using descriptive analysis techniques.